2015
DOI: 10.1165/rcmb.2015-0015oc
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Expression in Asthma. Association with Severity and Type 2 Inflammatory Processes

Abstract: Brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family, exists in several isoforms, which differentially impacts neuronal and immune cell survival and differentiation. The role of BDNF and its isoforms in asthma remains unclear. The objectives of this study were to compare the BDNF protein isoforms and specific splice variant expression in sputum and bronchoscopic samples from healthy control subjects and participants with asthma, and to relate these changes to findings in IL-13-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 45 publications
1
42
1
Order By: Relevance
“…We previously showed that BDNF acts like a growth factor, working in conjunction with inflammatory mediators relevant to asthma, such as TNF-␣ and IL-13, to modulate [Ca 2ϩ ] i (37) and ASM proliferation (7). In the airway, BDNF can be secreted by a variety of cell types, including immune cells, neurons, epithelial cells, and smooth muscle cells, and recently, BDNF expression and regulation, as well as its action via TrkB in these cells, have gained attention as a potentially significant mechanism in the pathogenesis of asthma (33,35,44,49). The data presented in the current study present a picture of complex regulation of endogenous BDNF expression and secretion by human ASM in the context of inflammation (represented by TNF-␣) and highlight a potential autocrine role for this neurotrophin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that BDNF acts like a growth factor, working in conjunction with inflammatory mediators relevant to asthma, such as TNF-␣ and IL-13, to modulate [Ca 2ϩ ] i (37) and ASM proliferation (7). In the airway, BDNF can be secreted by a variety of cell types, including immune cells, neurons, epithelial cells, and smooth muscle cells, and recently, BDNF expression and regulation, as well as its action via TrkB in these cells, have gained attention as a potentially significant mechanism in the pathogenesis of asthma (33,35,44,49). The data presented in the current study present a picture of complex regulation of endogenous BDNF expression and secretion by human ASM in the context of inflammation (represented by TNF-␣) and highlight a potential autocrine role for this neurotrophin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, enhanced BDNF expression in epithelium of severe asthmatics has garnered interest in the idea that local BDNF expression and effects may be important in asthma phenotypes (49). We have shown that ASM responds to exogenous BDNF with elevated intracellular Ca 2ϩ ([Ca 2ϩ ] i ) and cell proliferation, particularly in the presence of cytokines such as TNF-␣ and IL-13 (1,7,34,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the cellular source, Wang and colleagues previously showed Ca 21 -dependent regulation of BDNF secretion in human airway smooth muscle (ASM) (1). In contrast, we focused on epithelial cells and did not address ASM expression.…”
Section: Replymentioning
confidence: 99%
“…All these reports obviously raise questions regarding cell sources versus targets of BDNF. Watanabe and colleagues demonstrate a potential relationship between altered BDNF isoforms in airway epithelial cells with asthma severity (1). Here, the contribution of the Th2 cytokine IL-13 in regulating BDNF exon VIb splice variant expression in sputum and in epithelial cells points to bronchial epithelium as at least one source.…”
mentioning
confidence: 93%